SISTEM KENDALI HEMAT ENERGI PADA GEDUNG BERTINGKAT BERBASIS INTERNET OF THINGS (IoT) - Yunus Tjandi; Zulhajji (UNM Journal of Technology and Vocational, 2022)
Almost the entire structure that supports modern life is related to electrical energy. The reality on the ground illustrates that there are still many uses of electrical energy that are not well targeted, which causes many short circuit accidents. To prevent this, good and correct electrical knowledge is needed and must be added with the use of a control system based on the Internet of Things that is energy efficient and serves to secure the building and its contents. This study aims to: 1) create an Internet Of Things (IoT)-Based Energy-Efficient Control System Software that functions to control the use of electrical energy in high-rise buildings using a Smartphone, 2) produce an Energy-Efficient Control System Device using software that has been created , 3) create Interfaces and Applications for energy-efficient control system devices based on the Internet of Things (IoT) with the help of smartphones that function to control electrical devices in high-rise buildings, both from close range and remotely. Data collection in this study used interview techniques with control experts, literature techniques, and direct measurement techniques for the control devices used. The data analysis method used in this study is a logic-method, based on an Internet of Things (IoT)-based control system using aSmartphone. The results of the study show that: 1) The Internet Of Things (IoT)-Based Energy Saving Control System Software has worked well, this is evidenced by the operation of all control systems, both on the security system (MCB), as well as for various controlled loads, 2 ) The Internet Of Thingsbased Energy-Efficient Control System which is made to control the equipment has worked well, this has been proven in research trials using Smartphones, 3). Interface and Application of Control System based on Internet Of Things that is made to work well, and can control electrical equipment contained in a multi-storey building.